Efek Kedisiplinan dan Kinerja Karyawan terhadap Pengembangan Karir: Studi pada PT Kamaltex - Devi, Prajna Paramitha Chandra; Wijayanto, Petrus (Jurnal Maksipreneur, 2023)
Every economic sector is required to always move with the times to have an effect in the form of strong economic growth from time to time. In meeting these targets, each individual is required to have an attitude of discipline at work, so that the work carried out can be carried out optimally. Discipline indirectly plays a role in the career development of a worker. In the context of a worker's career development, not only is disciplined behavior at work needed, but also the performance factor of the worker. Career development is one of the goals or points that is highly anticipated by a worker, besides that the effect of applying discipline and improving performance will also cause feelings of job satisfaction in each worker. This study aims to examine the effects of discipline and employee performance on career development at PT Kamaltex. This research will use quantitative methods using secondary data in the form of data on the number of active employees and data on the length of service of employees and primary data in the form of data on the effects of discipline, and employee performance on job satisfaction. The results of this study state that employee discipline and performance influence the career development of employees.